2017
DOI: 10.7567/jjap.56.102301
|View full text |Cite
|
Sign up to set email alerts
|

Passivation of textured crystalline silicon surfaces by catalytic CVD silicon nitride films and catalytic phosphorus doping

Abstract: Silicon nitride (SiNx) films formed by catalytic chemical vapor deposition (Cat-CVD) and phosphorus (P)-doped layers formed by catalytic impurity doping (Cat-doping) are applied for the passivation of pyramid-shaped textured crystalline Si (c-Si) surfaces formed by anisotropic etching in alkaline solution. Lower surface recombination velocities (SRVs) tend to be obtained when smaller pyramids are formed on c-Si surfaces. P Cat-doping is effective for reducing the SRV of textured c-Si surfaces as in the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…26 • Antireflection coating and passivation layers in Si solar cells. 5,41,49 • Protection/encapsulation layers, sacrificial layers, diffusion barriers, and functional structures, including top encapsulation layers in IC devices and three-dimensional (3D) devices. 22 • Protection/encapsulation layers and spacers in DRAM.…”
Section: Ald Modeling and Mechanistic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 • Antireflection coating and passivation layers in Si solar cells. 5,41,49 • Protection/encapsulation layers, sacrificial layers, diffusion barriers, and functional structures, including top encapsulation layers in IC devices and three-dimensional (3D) devices. 22 • Protection/encapsulation layers and spacers in DRAM.…”
Section: Ald Modeling and Mechanistic Studiesmentioning
confidence: 99%
“…44 • Passivation and dielectric layers in interdigitated back-contact (IBC) Si solar cells. 49 Table II…”
Section: Ald Modeling and Mechanistic Studiesmentioning
confidence: 99%
“…Doping gases, such as phosphine (PH 3 ) and diborane (B 2 H 6 ), are catalytically decomposed at the hot surface of the filaments into phosphorous (P) and boron (B) radicals. , The radicals move from the filament surface to the sample surface and then diffuse into the silicon material films, forming a shallow depth doping layer with a thickness of 5–20 nm. Therefore, it is possible to replace the deposition of the doped silicon layer by Cat-doping on the intrinsic layer, which reduces the parasitic absorption of doped silicon layers. Former studies have shown that the material properties, such as conductivity and doping concentration, can be further tuned beyond the level that is achievable for as-grown films. ,, It has also been reported that the passivation quality of SHJ structures could be improved with Cat-doping on different interfaces, such as at the c-Si, a-Si:H­(i), and doped silicon layer surfaces in a SHJ structure. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Cat-doping can also improve the passivation quality of the passivated samples with symmetric structures of μc-Si:H(n)/a-Si:H(i)/c-Si/a-Si:H(i)/ μc-Si:H(n) and a-Si:H(n)/a-Si:H(i)/c-Si/a-Si:H(i)/a-Si:H(n) in which the interfaces of μc-Si:H(n) and c-Si are cat-doped, respectively. [10,[14][15][16] In this work, we investigate the phosphorus cat-doping on μc-Si:H(n), nc-SiO x :H(n), and μc-SiC:H(n) for the use in SHJ solar cells. The phosphorus distribution profiles of three silicon alloy films after cat-doping process were obtained by secondary ion mass spectrometry (SIMS).The impact of cat-doping on electrical property of silicon alloy films was evaluated from conductivity measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Cat‐doping can also improve the passivation quality of the passivated samples with symmetric structures of μc‐Si:H(n)/a‐Si:H(i)/c‐Si/a‐Si:H(i)/μc‐Si:H(n) and a‐Si:H(n)/a‐Si:H(i)/c‐Si/a‐Si:H(i)/a‐Si:H(n) in which the interfaces of μc‐Si:H(n) and c‐Si are cat‐doped, respectively. [ 10,14–16 ]…”
Section: Introductionmentioning
confidence: 99%